(untitled) (Pesquisa Odontológica Brasileira, 2002)
The aim of this study was to evaluate the effects of alternative filtration with the aluminum-zinc alloy in dental X-ray devices, regarding the energy spectrum, dose, contrast and image quality. This study was carried out comparing the conventional aluminum filter with aluminum-zinc alloy filters of various thicknesses and with different percentages of zinc in the alloy (2, 3, 4 and 5%). A conventional X-ray device operating with 60 and 70 kVp as well as D- and E-speed films were utilized in order to obtain images of a phantom and an aluminum step wedge. The utilization of Al-Zn filters resulted in a spectrum without hardening of beams. The rate of kerma in the air decreased 18.53%, without any alteration in contrast and image quality. The results revealed that the 2% Al-Zn alloy filter with 1.99 mm of thickness, utilized with the tension of 60 kVp and D-speed film, had the best performance. It reduced the rate of kerma without varying the indices of contrast and maintained image quality at acceptable levels, without increasing the time of exposure.